Automatic Portrait Segmentation for Image Stylization. (27th May 2016) - Shen, Xiaoyong; Hertzmann, Aaron; Jia, Jiaya; Paris, Sylvain; Price, Brian; Shechtman, Eli; Sachs, Ian
Abstract: Portraiture is a major art form in both photography and painting. In most instances, artists seek to make the subject stand out from its surrounding, for instance, by making it brighter or sharper. In the digital world, similar effects can be achieved by processing a portrait image with photographic or painterly filters that adapt to the semantics of the image. While many successful user‐guided methods exist to delineate the subject, fully automatic techniques are lacking and yield unsatisfactory results. Our paper first addresses this problem by introducing a new automatic segmentation algorithm dedicated to portraits. We then build upon this result and describe several portrait filters that exploit our automatic segmentation algorithm to generate high‐quality portraits.